PENINGKATAN PEMAHAMAN KONSEP DASAR IPS MAHASISWA PGSD MELALUI MODEL COOPERATIVE TIPE GI - Anggraini, Melani Septi Arista; Ismaniati, Christina; Mustadi, Ali (Universitas Djuanda, 2019)
Good education reflects the quality of the nation. A teacher is a spearheaded on the educational field to provide generation that has a good quality. In order to established a generation that has good quality, a quality learning method is needed. Therefore, PGSD students as prospective national educators have to understand the basics of learning in elementary schools. The study that is conducted at UST in the department of PGSDÂ found that the understanding of the basic concepts of social study is low. The aim of the study is to improve the understanding concept of social study to students in UST in the department of PGSD. This study uses Cooperative model type GI in lecture activities. The study is used classroom action research by engaging 2 cycles, each cycle has a duration about 2Ã—50 mins and conducted on 2 meetings. Subjects of the study were the writer as a researcher, lecturer, and students of Â UST in the department of PGSD. Data sources were taken from lecturer and students. Data were collected used test, observation, and interview technique. The data validity test is used triangulation. The data analysis technique that is used an interactive analysis that consisting of data collection, data reduction, data presentation and conclusion drawing. The result of the study shows that the use of GI able to improve the understanding of the basic concept of social study on the student in UST in department of PGSD. Lecturers may use the GI in the learning process to make students more active in study and to improve the understanding of students' conceptions.